Lessons from Africa's Social Funds, Public Works and Employment Projects - Frigenti, Laura (World Bank, Washington, DC, 2012)
The note focuses on the review of "Local solutions to regional problems: the growth of social funds and public works, and employment projects in Sub-Saharan Africa", which compares, and draws lessons from the African experience. It highlights three social funds in Zambia, Eritrea and Angola, and three urban works projects in Senegal, Benin, and Mauritania, and provides stakeholder views: it reports high impact on employment, income, and local capacity building; improved coordination between service providers; weak consideration to the sustainability of micro-projects; and, participatory inadequacies, at the expense of long-term sustainability. The note implies the greatest challenge these operations face, is the reconciliation of short-term, and long-term goals, and, beneficiary participation, and ownership should be key to social funds project design, with appropriate technical standards in design, construction, and supervision for micro-projects sustainability.